(untitled) (Quaestiones Disputatae: temas en debate, 2020)
This essay expresses a critical overview of a possible alternative education project based on the concept of an ecology of knowledge proposed by Boaventura de Sousa Santos. In turn, the document proposes a debate on the current situation of education in order to constitute a philosophical criticism that can inquire into the relations with knowledge, cultural criticism and the meaning of the human being present in the educational act. In view of this, the document begins with a description of the crisis of the paradigm of progress based on financial capitalism. Then it establishes possible confrontations with some postulates and ideas of Boaventura de Sousa Santos. Finally, it offers a possible characterization of Latin American pedagogy by considering the break with the indolent rationality implied by the proposal of the ecology of knowledge.